Topical space, heterotopias, pandemics and other accidents of space - Finocchi, Riccardo (E|C, 2021)
This contribution focuses on three key concepts developed through the analysis of some phenomena which became quite common, especially due to the COVID19 pandemic. The latter, in fact, has had a profound impact on the daily practices of human beings. The three concepts are: spatiality, city and mediality. The analysis of these concepts allows to reframe the semiotic relationship between topical spaces and heterotopias as a function of digital spaces. In this sense, some phenomena involving space will be clarified, including: the cities visited by drones during the pandemic or the extraordinary prayer that Pope Bergoglio celebrated in March 2020. Keywords: heterotopies, pandemics, space, drones, Bergoglio